2013
DOI: 10.14202/vetworld.2013.889-896
|View full text |Cite
|
Sign up to set email alerts
|

Disease alerts and forecasting of zoonotic diseases: an overview

Abstract: Epidemiologists are adopting new techniques by the use of Geographical Information System (GIS) to study a variety of animal and zoonotic diseases. Associations between satellite-derived environmental variables such as temperature, humidity, land cover type and vector density is used for disease prediction. Early warning systems rapidly detect the introduction or sudden increase in incidence of any disease of livestock which has the potential to develop into epidemic proportions and/or cause serious socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Veterinary epidemiologists are adopting these new techniques to study a variety of animal and zoonotic diseases (Kshirsagar et al 2013). These quite uncommonly utilized techniques are not known to have been previously applied in the area of CBPP epidemiology in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Veterinary epidemiologists are adopting these new techniques to study a variety of animal and zoonotic diseases (Kshirsagar et al 2013). These quite uncommonly utilized techniques are not known to have been previously applied in the area of CBPP epidemiology in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Cross boarder issues in transferring diseases is prevalent in India. India has developed its own ADMAS‐Epitrak software using database, GIS and statistical tools for recording, reporting and analysis of transboundary animal and infectious zoonotic diseases such as Avian Influenza (AI) (FAO 2001) 24 . Recently, India has also launched a GIS mapping system called Animal Disease Referral Expert System (NADRES), the first of its kind in South Asia, for the surveillance of infectious zoonotic diseases such as anthrax and HPAI (SAARC/FAO 2011) 25 .…”
Section: Results (Literature Review)mentioning
confidence: 99%
“…Musa et al (2013) also reported that the most important application of GIS in the field is in the identification of disease clusters. Despite the fact that the technique has been adopted in the study of various zoonoses in the world (Kshirsagar et al, 2013), its application is still in its infancy stage in Nigeria, especially in the northern part of the country (Alhaji et al, 2016). Amongst the few work done using this technique in Nigeria is the mapping out the burden of contagious bovine pleuropneumonia (CBPP) carried out by Alhaji et al (2016) in north-central Nigeria.…”
Section: Discussionmentioning
confidence: 99%